Advances in nanotechnology application in biosafety materials: A crucial response to COVID-19 pandemic - Rasmi V. Morajkar; Akhil S. Kumar; Rohan K. Kunkalekar; Amit A. Vernekar (Elsevier, 2022)
The outbreak of coronavirus disease 2019 (COVID-19) has adversely affected the public domain causing unprecedented cases and high mortality across the globe. This has brought back the concept of biosafety into the spotlight to solve biosafety problems in developing diagnostics and therapeutics to treat COVID-19. The advances in nanotechnology and material science in combination with medicinal chemistry have provided a new perspective to overcome this crisis. Herein, we discuss the efforts of researchers in the field of material science in developing personal protective equipment (PPE), detection devices, vaccines, drug delivery systems, and medical equipment. Such a synergistic approach of disciplines can strengthen the research to develop biosafety products in solving biosafety problems.